Strategi Komunikasi Kyai dalam Upaya Menarik Minat Masyarakat untuk Melanjutkan Pendidikan Putra-Putrinya di Pondok Pesantren - Indah Yulianti; Teddy Khumaedi (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2024)
The lack of morals and religious education in adolescents can lead to delinquency and freedom in choosing friends that can damage the future of the teenager. It is undeniable that parents want children who are educated, both in general and religious, both can be obtained within the scope of Islamic boarding schools. The purpose of this writing is to find out the communication carried out by the kyai so that the community prefers to continue their sons and daughters' education at the Irsyadut Tholibien Islamic boarding school. The data used are primary and secondary data, while data collection uses observation, interview and documentation techniques, then the data is analyzed using a qualitative descriptive approach. This study proves that the communication strategy used by the kyai in an effort to increase public interest in continuing their sons and daughters' education at Islamic boarding schools is choosing and determining communicators, determining target targets, message composition techniques, and selecting media or communication channels. Then using an organizational communication approach in the form of internal and external.